Cardiorespiratory fitness (CRF) and its relationship with maximum oxygen consumption (VO2max) among 16-year-old junior players at Zakho football club - Abdulsatar, Athraa Abdulelah (Universitas Tanjungpura, 2025)
Background and Study Aim. Cardiorespiratory fitness (CRF) plays a crucial role in modern football performance, particularly in youth development where proper assessment and monitoring can significantly impact long-term athletic potential. While laboratory-based measurements of maximum oxygen consumption (VO2 max) are accurate, there is a need to validate practical field-based testing methods for youth players, especially in regions with unique environmental conditions like Iraqi Kurdistan. The present study investigated the relationship between CRF and VO2 ma among 16-year-old football players at Zakho Football Club.Material and Methods. The descriptive correlational method was employed to examine the relationship between cardiorespiratory fitness CRF and VO2 max in 16-year-old junior football players. A random sample of twenty players was selected from a population of thirty-two players. The research utilized multiple assessment tools including the Cooper 12-minute test for CRF evaluation, heart rate monitoring through Garmin fÄ“nix ® 7 devices for measuring cardiovascular responses, and Cooper